2014
DOI: 10.4103/0976-237x.137900
|View full text |Cite
|
Sign up to set email alerts
|

Amnion membrane for coverage of gingival recession: A novel application

Abstract: Introduction:Amnion allograft has been used in the field of medicine for its exceptional wound-modulating properties. However, in the field of dentistry, only a limited number of reports have explored its potential in healing of oral wounds.Materials and Methods:Amnion allograft in conjunction with coronally advanced flap has been used in the management of gingival recession.Results:A complete coverage along with excellent esthetics and an improvement in gingival biotype was observed at 6 months postoperativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 4 publications
2
24
1
1
Order By: Relevance
“…In the amnion group the results are found to be similar with the studies done by Ghahroudi et al [15] and Gurinsky [7] who concluded that amnion membrane have comparable results as connective tissue graft and can be used as an alternative to autogenous grafts respectively. Shah et al [13] in a case report observed enhanced wound healing and esthetics with amnioin membrane.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the amnion group the results are found to be similar with the studies done by Ghahroudi et al [15] and Gurinsky [7] who concluded that amnion membrane have comparable results as connective tissue graft and can be used as an alternative to autogenous grafts respectively. Shah et al [13] in a case report observed enhanced wound healing and esthetics with amnioin membrane.…”
Section: Discussionmentioning
confidence: 97%
“…The basement membrane contains collagen type III, IV and V and cell adhesion bioactive factors including fibronectin and laminins (mainly Laminin 3). It helps in soft tissue healing, modulates angiogenesis, cicatrisation, epithelization and facilitated migration [13].…”
Section: Discussionmentioning
confidence: 99%
“…Human amnion membrane has excellent biologic properties and is now increasingly used in root coverage procedures sandwiched beneath a coronally repositioned flap. [7][8][9] As a potential allograft for root coverage procedures, it is important to understand how long the amnion membrane could survive at the defect site. In our study we observe the resorption rate of human amnion membrane in comparison to commercially available bovine collagen membrane.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mean value from 6 months to 18 months was statistically nonsignificant ( P = 0.343). These results are in the accordance to the study of Mehta et al .,[ 23 ] Shah et al .,[ 24 ] and Gurinsky,[ 25 ] who stated that processed dehydrated allograft amnion may provide an effective alternative to autograft tissue in the treatment of shallow-to moderate Miller Class I gingival recession defects. Thus, the authors concluded that the self-adherent nature of the amnion allograft significantly reduced surgical time and made the procedure easier to perform relative to techniques involving the use of autograft or allograft dermis tissue.…”
Section: Discussionmentioning
confidence: 99%